Criteria for evaluation of incapacity to work in heart failure - Torres, Rafael Augusto Tamasauskas; Cintra, Raquel Barbosa; Sá, Eduardo Costa (Revista de Medicina, 2015)
ABSTRACT: Introduction: Social Security in Brazil, is a social insurance that guarantees the income of the insured when he loses his job capacity. Among the benefits granted have a disability pension, and for being granted the insured it must undergo medical examination to prove their total and permanent disability. Fourteen percent of disability pensions granted in the last three years were due to diseases of the circulatory system, and the final pathway of the majority of these diseases is heart failure. Objective: To identify criteria for determining total and permanent disability in patients with congestive heart failure in social security skills. Methodology: Literature review, no limit date, held from April to August 2014, using the following key words: heart failure, disability and retirement, the following databases: Pubmed/Medline; BVS (Virtual Health Library); Scopus; Web of Science; and Cochrane. Pension legislation was investigated. Results: Heart failure is crippling to mobility, complex tasks and self-care tasks, and present with moderate or severe cognitive impairment. Heart failure as a complication after infarction is a strong indicator for early retirement, taking as a positive prognostic factor for return to work age less than 60 years, a fraction ejection greater than 35%, lack of funding during the removal, absence of anxiety attacks and work with low physical demands. Discussion: The Grade III or IV heart failure progresses with a disability which, if permanent, will right to disability retirement. Complementary exams should not be used in isolation, and greater than 60 years old, female and high workload are poor prognostic factors. Conclusion: The evaluation of work capacity in heart failure should be taken into consideration clinical, ejection fraction, the cognition, physical demands of the job and conditions of this return, the age and NYHA functional classification or Social Security classification used.